Felid Cardiopulmonary Nematodes: Dilemmas Solved and New Questions Posed - Donato Traversa; Simone Morelli; Angela Di Cesare; Anastasia Diakou (Pathogens, 2021)
In the past decade cardiopulmonary nematodes affecting felids have become a core research topic in small animal parasitology. In the late 2000s, an increase in studies was followed by unexpected findings in the early 2010s, which have stimulated research teams to start investigating these intriguing parasites. Prolific scientific debate and exchanges have then fostered field and laboratory studies and epizootiological surveys. New data have improved basic and applied knowledge, solved dilemmas and posed new questions. This article discusses the past and present background to felid cardiopulmonary nematodes after the last few years of intense scientific research. New data which have demonstrated the key role of Aelurostrongylus abstrusus and Troglostrongylus brevior in causing respiratory infections in domestic cats, and on the nil to negligible current importance of other species, i.e., Troglostrongylus subcrenatus, Oslerus rostratus and Angiostrongylus chabaudi, are presented. Biological information and hypothesized alternative routes of infection are analysed and discussed. Novel identification and taxonomical data and issues are reported and commented upon. On the whole, recent biological, ecological and epizootiological information on felid metastrongyloids is critically analysed, with the aim to answer outstanding questions, stimulate future studies, and underline new research perspectives.